Implementasi Pendidikan Karakter Di Era Globalisasi Melalui Pembelajaran PPKn Siswa SMK Cendana DDI Samarinda - Odilian Syah; Marwiah Marwiah; Endang Herlah; Jawatir Pardosi; Suryaningsi Suryaningsi; Warman Warman (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2024)
This study aimed to identify the implementation of character education in the era of globalisation through PPKN learning for students of SMK Cendana DDI Samarinda, Samarinda City. This type of research is descriptive qualitative. The focus of this research is to find out how the planning, implementation and values that appear in learning at SMK Cendana DDI Samarinda. The data collection techniques used are observation, interviews and documentation. Data analysis techniques used are data reduction, data display, data presentation and drawing conclusions. The results of this study indicate that the implementation of character education in SMK Cendana students still has many shortcomings in the form of planning that is documented very well but only continues the previous teacher's teaching program, the implementation of character education is very good in the field of delivery and giving examples but in the absence of documentation of measuring student development teachers do not understand how to see the progress of character education in the classroom, the value that arises from the implementation of character education in the classroom has had a great impact on student understanding but because smk cendana is a vocational school students do not pay full attention and focus more on their major lessons